Special Medians of a Triangle

Geometry Level 3

In triangle A B C ABC , D D is the midpoint of A C AC and E E is the midpoint of A B AB . B D BD and C E CE are perpendicular to each other and intersect at the point G G . If A B = 7 AB = 7 and A C = 9 AC = 9 , what is the value of B C 2 BC^2 ?


The answer is 26.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

Clark Makmur
May 20, 2014

Draw an extra line between D E DE

Triangle A D E ADE is similar to Triangle A B C ABC

If we say B C BC is x x , means D E DE is x 2 \frac x2

We can say :

x 2 x^2 = B G 2 BG^2 + C G 2 CG^2

( x 2 ) 2 (\frac x2)^2 = D G 2 DG^2 + E G 2 EG^2

Adding them up would be :

5 4 x 2 \frac 54x^2 = ( B G 2 + E G 2 ) (BG^2 + EG^2) + ( C G 2 + D G 2 ) (CG^2 + DG^2)

5 4 x 2 \frac 54x^2 = ( 7 2 ) 2 (\frac 72)^2 + ( 9 2 ) 2 (\frac 92)^2

5 4 x 2 \frac 54x^2 = 49 4 \frac {49}{4} + 81 4 \frac {81}{4}

5 x 2 5x^2 = 49 + 81 49+81

x 2 x^2 = 130 5 \frac {130}{5} = 26 26

If C E CE is the median of the triangle, and G G is the intersections of the medians (also known as the centroid), do you know how to show that C G = 2 G E CG = 2 GE ?

Calvin Lin Staff - 7 years ago
Tianbo Chen
May 20, 2014

We know that \overline{BD} and \overline{EC} are medians because they connect the midpoint of a side of the triangle and the opposite vertex. Therefore the centroid (point G) separates \overline{EC} into ratios of 1:2 and \overline{BD} into ratios of 1:2. Set \overline{BG} as 2x, \overline{GD} as x, \overline{CG} as 2y and \overline{GE} as y. By Pythagorean Theorem, x^2 + 4y^2 = (\frac{9}{2})^2 and 4x^2 + y^2 = (\frac{7}{2})^2. We desire 4x^2 + 4y^2 because this will equal (\overline{BC})^2. Adding both equations together leads to 5x^2+5y^2 = \frac{65}{2}. 4x^2+4y^2 = 26.

Anuj Balaji
May 20, 2014

Let BD be 3x and CE be 3y
So by the property of Centroid,
B G G D \frac {BG}{GD} = C G G D \frac {CG}{GD} = 2 1 \frac {2}{1} Also,
B E 2 BE^{2} = E Y 2 + B Y 2 EY^{2} + BY^{2}
7 2 2 \frac {7}{2}^{2} = y 2 + ( 2 x ) 2 y^{2} + (2x)^{2}
49 4 \frac {49}{4} = y 2 + 4 x 2 y^2 + 4x^2 Eq. No.: 01
Similarly,
C D 2 CD^{2} = G D 2 + C G 2 GD^{2} + CG^{2}
9 2 2 \frac {9}{2}^{2} = x 2 + ( 2 y ) 2 x^{2} + (2y)^{2}
81 4 \frac {81}{4} = x 2 + 4 y 2 x^2 + 4y^2 Eq. No.: 02
Upon adding Eq. 1 and Eq. 2 we get,
5 × ( x 2 + y 2 ) 5 \times (x^2 + y^2) = 130 4 \frac {130}{4}
Upon multiplying this by 4 5 \frac {4}{5} we get,
4 x 2 + 4 y 2 4x^2 + 4y^2 = 26
( 2 x ) 2 + ( 2 y ) 2 (2x)^2 + (2y)^2 = 26
B G 2 + G C 2 BG^{2} + GC^{2} = 26
B C 2 BC^{2} = 26




Sed Holaysan
May 20, 2014

Because angles BGE and CGD are right angles, it can be concluded via the Pythagorean Theorem that E G 2 EG^2 + B G 2 BG^2 = 3. 5 2 3.5^2 , and C G 2 CG^2 + D G 2 DG^2 = 4. 5 2 4.5^2 . Furthermore, D G 2 DG^2 + E G 2 EG^2 = D E 2 DE^2 . Because DE is the midline of triangle ABC (D and E are respective midpoints of the sides they are on), its length must be half that of BC. Finally, B G 2 BG^2 + C G 2 CG^2 = B C 2 BC^2 . Substituting and simplifying: B C 2 BC^2 = B G 2 BG^2 + C G 2 CG^2 , B C 2 BC^2 = 3. 5 2 3.5^2 - E G 2 EG^2 + 4. 5 2 4.5^2 - D G 2 DG^2 , B C 2 BC^2 = 32.5 - ( E G 2 EG^2 + D G 2 DG^2 ), B C 2 BC^2 = 32.5 - E D 2 ED^2 , B C 2 BC^2 = 32.5 - ( B C / 2 ) 2 (BC/2)^2 , ( 5 / 4 ) B C 2 (5/4)BC^2 = 32.5, B C 2 BC^2 = 26

Ruslan Abdulgani
May 20, 2014

Let CG=a, GE=b, GB=c, GD =d, and BC=x. Using Pythagoras, we have a^2 + c^2 = x^2 ...(1), a^2 + d^2 = 4.5^2 .....(2), and b^2 + c^2 = 3.5^2 ........(3). We add (2) and (3) these 3 to get a^2+b^2+c^2+d^2 = 4.5^2+3.5^2. Substitute (1) to this equation. then we have x^2 + b^2+d^2 = 4.5^ + 3.5^. But b^2+d^2 is (DE)^2 which is (0.5 x)^2. So we have 0.25x^2 + x^2 = 32.5, then we find x^2 = (BC)^2 = 26

Carlo Furlanetto
May 20, 2014

Noting that the triangles EBG, CGD, GCB and DEG are right triangles we deduce the validity of the following reports:

EB^2-BG^2=GE^2

DC^2-CG^2=GD^2

CG^2+GB^2=CB^2

DG^2+GE^2=DE^2

So:

EB^2-BG^2+DC^2-CG^2=GE^2+GD^2=DE^2

So:

EB^2+DC^2-(BG^2+CG^2)=DE^2,

EB^2+DC^2-CB^2=DE^2.

Observing that:

CB^2=4DE^2 (CB=2DE)

we may write:

EB^2+DC^2-CB^2=(CB^2)/4.

SO:

EB=7/2, CD=9/2

CB^2=26

Mirza Baig
May 20, 2014

Medians are divided in 2:1 by centroid, thus

GE=b and GC=2b for some a and b GD=a and GB=2a

By Pythagoras Theorem,

(2a^2) + (b^2) = ((7/2)^2), (2b^2) + (a^2) = ((9/2)^2)

Solving the two for positive a and b, we get

a=(sqrt(23/3))/2 and b=(sqrt(55/3))/2

Again by Pythagoras,

(BC)^2 = (2a)^2 + (2b)^2 = 78/3 = 26

Calvin Lin Staff
May 13, 2014

Since B D BD and C E CE are medians, thus A E = E B AE=EB , A D = D C AD=DC and D E DE is parallel to B C BC . It also follows that triangles A D E ADE and A C B ACB are similar, thus B C D E = A B A E = 2 \frac{BC}{DE} = \frac{AB}{AE} = 2 B C = 2 D E \Rightarrow BC = 2DE . Since D E DE is parallel to B C BC thus E D B = D B C \angle EDB = \angle DBC and D E C = E C B \angle DEC = \angle ECB , which implies that triangles D E G DEG and B C G BCG are similar by angle-angle-angle and a factor of B C D E = 2 \frac{BC}{DE}=2 .

Let G D = x GD = x and G E = y GE = y , so we have B G = 2 x BG = 2x and C G = 2 y CG = 2y . Applying the Pythagorean theorem on triangles G E B GEB , G D C GDC and G B C GBC , we have A B 2 4 = E B 2 = 4 x 2 + y 2 \frac{AB^2}{4} = EB^2 = 4x^2 + y^2 , A C 2 4 = D C 2 = x 2 + 4 y 2 \frac{AC^2}{4} = DC^2 = x^2 + 4y^2 and B C 2 = 4 x 2 + 4 y 2 BC^2 = 4x^2 + 4y^2 . Adding the first two equations, we have

A B 2 + A C 2 4 = 5 x 2 + 5 y 2 = 5 4 B C 2 B C 2 = A B 2 + A C 2 5 = 7 2 + 9 2 5 = 26 \begin{aligned} \frac{AB^2 + AC^2}{4} &= 5x^2 + 5y^2 \\ &= \frac{5}{4}BC^2 \\ BC^2 &= \frac{AB^2 + AC^2}{5} \\ &= \frac{7^2 + 9^2}{5} \\ &= 26 \\ \end{aligned}

Ahmad Saad
Nov 28, 2016

In triangle A B C ABC , D D is the midpoint of A C AC and E E is the midpoint of A B AB . B D BD and C E CE are perpendicular to each other and intersect at the point G G .

Because G G is median and B D BD and C E CE are perpendicular to each other, implies C G = 2 E G CG = 2EG and B G = 2 D G BG = 2DG and we got 3 right triangle of C G D CGD , B G E BGE and B G C BGC .

Just do with Pythagorean theorem on each triangle.

Let see in triangle C G D CGD

C G 2 + D G 2 = C D 2 CG^2 + DG^2 = CD^2

because C D = C A 2 = 9 2 CD=\frac {CA}{2}=\frac {9}{2} and D G = B G 2 DG=\frac {BG}{2}

C G 2 + ( B G 2 ) 2 = ( 9 2 ) 2 CG^2 + (\frac {BG}{2})^2 = (\frac {9}{2})^2

4 C G 2 + B G 2 = 9 2 4CG^2 + BG^2 = 9^2 .. (1)

in triangle B G E BGE

B G 2 + E G 2 = B E 2 BG^2 + EG^2 = BE^2

because B E = B A 2 = 7 2 BE=\frac {BA}{2}=\frac {7}{2} and E G = C G 2 EG=\frac {CG}{2}

B G 2 + ( C G 2 ) 2 = ( 7 2 ) 2 BG^2 + (\frac {CG}{2})^2 = (\frac {7}{2})^2

4 B G 2 + C G 2 = 7 2 4BG^2 + CG^2 = 7^2 ... (2)

and in triangle B G C BGC

B C 2 = C G 2 + B G 2 BC^2 = CG^2 + BG^2 ... (3)

Let's sum (1) and (2) we'll got

5 B G 2 + 5 C G 2 = 9 2 + 7 2 5BG^2 + 5CG^2 = 9^2 + 7^2 divide it with 5

B G 2 + C G 2 = 9 2 + 7 2 5 BG^2 + CG^2 = \frac{9^2 + 7^2}{5}

and subtitute to (3)

B C 2 = 9 2 + 7 2 5 = 26 BC^2 = \frac{9^2 + 7^2}{5} = 26

Justin Luo
May 20, 2014

BD is a median of the triangle, so BG = 2 DG. Similarly, CG = 2 EG. Let DG = a and EG = b. Then, by Pythagorean theorem on triangle BGE, 4a^2+b^2=(7/2)^2=49/4. By Pythagorean theorem on triangle CGD, a^2+4b^2=(9/2)^2=81/4. Adding gives 5a^2+5b^2=130/4=65/2, so a^2+b^2=13/2.

What we want to find is BC^2 which is 4a^2+4b^2 by Pythagorean theorem again. This is 4*13/2=26.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...